Audit committee and auditor independence: the bankers' perception - Muhamad Sori, Zulkarnain; Mohamad, Shamsher (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This paper examines the perception of bankers on contribution of audit committees towards external auditor independence in public listed companies. All Malaysian public listed companies are required to establish an audit committee as a measure to improve on the internal control mechanism that can help improve the corporate governance practices of firms. Postal questionnaires and interview surveys were used to solicit the perception and views of loan officers. The majority of the respondents believe that auditor independence is preserved with the presence of an actively functioning audit committee. This implies favourably on the corporate governance reforms initiated by the government after the 1998 financial crisis.